Reclaiming his legacy - Wade, Dani (Wade, Dani. Louisiana legacies, 2020)
"He'll go to any lengths for his family... even seduction. He'd set the perfect trap... Until he got caught. Blake Boudreaux's sex appeal is legendary--so is his family loyalty. When his father tasks him with retrieving a beloved heirloom to save their finances, the New Orleans playboy agrees, even if it means seducing Madison Armantine. The beautiful philanthropist is helpless against his strong arms and sultry Southern drawl, even as she suspects ulterior motives. But what if Madison isn't the only one falling in love?"--Provided by publisher.